Clear cell calcifying epithelial odontogenic tumor: A rare case report - Jincy Thomas; Valsa Thomas; Nileena R Kumar; Sharafuddeen (Wolters Kluwer Medknow Publications, 2008)
The calcifying epithelial odontogenic tumor (CEOT) is a benign epithelial odontogenic lesion that accounts for less than 1% of all odontogenic tumors. Clear cell variant of CEOT is extremely rare with only fifteen cases documented till date. The occurrences of clear cells may prove to be a sign of increased tumor aggressiveness, indicating the need for a more radical surgical approach.